Spectral modelling of multicomponent landscapes in the Sahel - Hanan, N.P.; Prince, S.D.; Hiernaux, Pierre H.Y. (Informa UK Limited, 1991)
Certain landscapes in the Sahel and elsewhere consist of a 'checkerboard' arrangement of vegetated and non-vegetated areas in which there may be several spectrally distinct vegetation and bare ground components. When individual components form large spatially coherent patches, and the vertical dimension of the vegetation is small, spectral interactions between components are negligible. The influence of any one component on the average reflectance of the landscape can then be described by its spectral properties and relative area using simple additive mixture models. These models can be extended to the vegetation indices. The spatial average normalized difference vegetation index (NDVI) is a function of the brightness (red plus near-infrared reflectances), the NDVI and the fractional cover of the components. In landscapes wher soil and vegetation can be considered the only components, the NDVI-brightness model can be inverted to obtain the NDVI of the vegetation. Aerial photoradiometer data from Mali, West Africa were used to determine the red and near-infrared component reflectances of soil and vegetation. The derived soil cmponent reflectances were well correlated with ground measurements. The relationship between the vegetation component NDVI and plant cover was better than NDVI of the entire landscape and plant cover. The usefulness of this modelling approach depends on the existence of clearly distinguishable landscape components. The method resolves the spectral properties of individual components, but the vegetation component, while free of the effect of bare ground components, is still affected by the underlying soil.